Joint strength of Ag–9Pd–9Ga brazed interconnect and anode-supported electrolyte for solid-oxide fuel cell applications. (September 2018) - Chao, Chih-Long; Chu, Chun-Lin; Fuh, Yiin-Kuen; Hsu, Ray-Quen; Lee, Shyong; Cheng, Yung-Neng
A newly developed Ag–9Pd–9Ga active filler was vacuum brazed, and the mechanical properties between the metallic interconnects (SS430, Crofer22 APU, Crofer22 H) and a Ni–yttria-stabilized zirconia cermet anode were systematically investigated. The results indicate that the bonding between metal and cermet is well established and that the interface is smooth. The joint strength evaluated at both 25 ℃ and 800 ℃ under shear and tensile loading conditions confirmed that the brazed Ag–9Pd–9Ga sealant compared favorably with its commercially available glass-ceramic GC-9 counterpart.